THE Factors In Building Employee Commitment: Mediating Role Of Job Satisfaction At Bank Central Asia. - Bambang Kustiawan; Kazan Gunawan; Ma'ruf Akbar (IJHCM (International Journal of Human Capital Management), 2021)
The condition of the use of the logistics workforce in the development of human resources of the TNI can still occur imbalances resulting from the aspects that’s not synergized well affecting the improvement of the quality of human resources of the TNI. The purpose of this study is to gather information related to the implementation evaluation results of the use of the logistics workforce in the construction of Human Resources in TNI with its evaluation by using William Dunn policy evaluation with evaluation criteria such as effectiveness, adequacy, alignment, responsiveness and accuracy. The qualitative method is used under the design of case study research. This research shows that from the evaluation of the implementation of the logistics workforce usage in the construction of TNI Human Resources in supporting the main tasks of the Indonesian National Army Headquarter with the findings: (1) The effectiveness of the use of logistics workers has a strategic function in achieving the performance of the TNI logistics workforce (2) The efficiency of the use of logistics workforce with diverse contributions, starting from planning, implementation and evaluation of logistical support, (3) Adequacy is interpreted to achieve conducive policy results, (4) Alignment/Justice leads to the issue of balance of results obtained will be comparable to the contribution given, (5) Responsivity cultures optimal service as TNI Logistics Staff, and (6) Accuracy of carrying out work by the respective task areas is in lined with the objectives of the implementation of activities to support the main tasks of the TNI Keywords: Policy Evaluation, Labor Use, Human Resources Development of the TNI